Analisis Sikap Orang Tua Terkait MP-ASI Terhadap Kejadian Diare Berulang Pada Toddler di Kabupaten Bogor - Susiana Jansen; Lusyta Puri Ardhiyanti; Rokhaidah Rokhaidah; Lina Ayu Marcelina; Mutiara Zahra; Tatu Latipah; Nathaniella Arafah; Khanza Hanaya Chairunisa (Jurnal Ners, 2026)
The WHO states that diarrhea is among the top five causes of death in infants and children. In Indonesia, diarrhea is also an endemic health problem and has the potential to cause an Extraordinary Event (KLB), increasing infant and toddler mortality rates. In West Java, particularly Bogor Regency, the prevalence of diarrhea remains alarming. Mothers' attitudes toward complementary feeding (MP-ASI) are closely related to the practice of providing complementary feeding. Inappropriate attitudes and practices in providing complementary feeding, parenting styles, and recurrent illnesses, especially diarrhea, will further worsen the nutritional status of Indonesian children. The purpose of this study was to examine the influence of maternal attitudes regarding MP-ASI on the incidence of diarrhea in Bogor Regency, West Java. Inclusion criteria for this study included: 1) a parent (mother) and a toddler aged 13–24 months; 2) a parent (mother) who can read. The sample size for this study was calculated using the Lemeshow formula, with 102 respondents.. This study used a cross-sectional method with two variables, namely Independent and Dependent. The measurement tools used in this study were a questionnaire sheet and a WHO nutritional status chart. The results of the statistical test obtained a p value = 0.319 (p > 0.05). This indicates that there is no significant relationship between maternal attitudes regarding complementary feeding and the incidence of diarrhea in toddlers. This means, in this study, maternal attitudes towards the provision of complementary feeding have not been statistically proven to be related to the presence or absence of diarrhea in toddlers. Keywords: complementary feeding, diarrhea, toddlers.